2020
DOI: 10.1093/biolinnean/blaa167
|View full text |Cite
|
Sign up to set email alerts
|

Sister species, different histories: comparative phylogeography of two bird species associated with Amazonian open vegetation

Abstract: Although the expansion of open vegetation within Amazonia was the basis for the Forest Refugia hypothesis, studies of Amazonian biota diversification have focussed mostly on forest taxa. Here we compare the phylogeographic patterns and population history of two sister species associated with Amazonian open-vegetation patches, Elaenia cristata and Elaenia ruficeps (Aves: Tyrannidae). We sampled individuals across Amazonia for both species, and in the central Brazilian savannas (Cerrado) for E. cristata. We sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 52 publications
5
15
0
Order By: Relevance
“…The Branco River is a white-water river that separates Aracá from Uatumã and Viruá and, together with its floodplains covered by seasonally flooded várzea vegetation, appear to have a stronger resistance for campina's specialist birds (Capurucho et al 2013;Matos et al 2016). Furthermore, as suggested by haplotype network and migration rates, both previously (Ritter et al 2020) and in this study, this river is also a barrier for E. ruficeps, which may have limited historical migration for Aracá populations. Analyses of sedimentary deposits and regional geomorphology suggested that a long segment of the Branco River was established in Late Pleistocene (Cremon et al 2016).…”
Section: Genetic Diversity and Population Structure: Historical Influsupporting
confidence: 58%
See 2 more Smart Citations
“…The Branco River is a white-water river that separates Aracá from Uatumã and Viruá and, together with its floodplains covered by seasonally flooded várzea vegetation, appear to have a stronger resistance for campina's specialist birds (Capurucho et al 2013;Matos et al 2016). Furthermore, as suggested by haplotype network and migration rates, both previously (Ritter et al 2020) and in this study, this river is also a barrier for E. ruficeps, which may have limited historical migration for Aracá populations. Analyses of sedimentary deposits and regional geomorphology suggested that a long segment of the Branco River was established in Late Pleistocene (Cremon et al 2016).…”
Section: Genetic Diversity and Population Structure: Historical Influsupporting
confidence: 58%
“…More refined studies on habitat permeability for white-sand vegetation birds are needed to develop more accurate isolation by resistance models. Our results suggest that although dispersal ability of E. ruficeps is at least to certain degree restricted through intervening vegetation types (Ritter et al 2020), it is still greater than overall dispersal ability for most terra-firme forest birds (Menger et al 2017;Menger et al 2018), but dispersal ability of E. ruficeps is lower when compared to dispersal of savanna birds (Bates et al 2003;Ritter et al 2020). In a previous study comparing the population structure of E. ruficeps with its sister species E. cristata, it was evident that E. cristata populations that occur in savanna, have a low population structure indicating a higher mobility than E. ruficeps (Ritter et al 2020).…”
Section: Genetic Diversity and Population Structure: Contemporary Infmentioning
confidence: 75%
See 1 more Smart Citation
“…Landscapes can vary in ways that affect both the phenology of resources (time) or availability of habitat (space); such variability can be tracked if conditions change at a pace that populations could respond to. Examples of this include species adapted to annually ephemeral or temporally patchy habitats such as wetlands and grasslands; species accustomed to such environments may have dispersal strategies that predispose them to better track climate (e.g., Elaenia cristata - Ritter et al, 2021). In other cases, habitat and resources are spatially patchily distributed, and the ability of species to respond to changing conditions may be more taxon-specific for those that rely on spatiotemporal heterogeneity that is naturally patchy.…”
Section: Figurementioning
confidence: 99%
“…In other cases, habitat and resources are spatially patchily distributed, and the ability of species to respond to changing conditions may be more taxon-specific for those that rely on spatiotemporal heterogeneity that is naturally patchy. Examples of this include habitat specialists in naturally patchy habitats such as Amazonian white sand habitats (e.g., Elaenia ruficeps - Ritter et al, 2021).…”
Section: Figurementioning
confidence: 99%